Zn-Al-Mg-based hot-dip plated steel sheet
By adjusting the chemical composition and structure of the hot-dip plating layer of the Zn-Al-Mg-based hot-dip plating steel plate, the problem of insufficient gloss and corrosion resistance of the hot-dip plating layer in the prior art is solved, and better metal gloss and Corrosion resistance enhances its application value in manufacturing.
Patent Information
- Application Number
- CN202380044360.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-10
AI Technical Summary
When Zn-Al-Mg hot-dip plating steel plates are used in automobiles, home appliances, building materials and other fields, it is difficult for the prior art to achieve the simultaneously improvement of the metallic gloss and corrosion resistance of the hot-dip plating, resulting in insufficient glossy surface appearance.
By adjusting the chemical composition of the hot-dip plating layer, the Al content is between 10-22 mass%, the Mg content is between 1.0-10 mass%, and the [Zn phase] area component of the plating structure is less than 20% on the surface of the plating layer. It can be optionally contained in Si, Ni, Ti and other elements, and optimize the thickness and structure of the coating to improve metallic gloss and corrosion resistance.
The Zn-Al-Mg-based hot-dip plate with excellent metallic gloss and corrosion resistance on the surface of the hot-dip plated layer has been achieved, which has enhanced its application value in the manufacturing industry.
Smart Images

Figure CN119301292A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a Zn-Al-Mg-based hot-dip plated steel sheet having a glossy appearance.
[0002] This application claims priority based on Japanese Patent Application No. 2022-094346 filed in Japan on June 10, 2022, and the contents are incorporated herein by reference. Background Art
[0003] Hot-dip galvanized steel sheets are used as steel sheets with good corrosion resistance. Hot-dip galvanized steel sheets, which are representative examples of hot-dip galvanized steel sheets, are widely used in various manufacturing industries such as automobiles, home appliances, and building materials. In addition, in order to further improve the corrosion resistance of hot-dip galvanized steel sheets, highly corrosion-resistant hot-dip galvanized steel sheets containing Al and Mg in the hot-dip galvanized layer have been proposed. For example, Zn-Al-Mg hot-dip galvanized steel sheets are proposed in Patent Documents 1 to 3.
[0004] However, the hot-dip Zn-Al-Mg steel sheet contains four main phases and structures in the hot-dip coating, namely, [Al phase], [Zn phase], [MgZn2 phase], and [ternary eutectic structure of Al / MgZn2 / Zn]. In addition, when Si is contained in the hot-dip coating in addition to Zn, Al, and Mg, five main phases and structures including [Mg2Si phase] are contained in addition to the above four phases and structures. In this way, since a plurality of phases and structures are mixed in the hot-dip coating of the Zn-Al-Mg steel sheet, the surface of the hot-dip coating has a pear-skin-like appearance.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 10-226865
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 10-306357
[0009] Patent Document 3: Japanese Patent Application Publication No. 2004-68075 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Zn-Al-Mg hot-dip plated steel sheets are widely used in various manufacturing industries such as automobiles, home appliances, and building materials, just like hot-dip galvanized steel sheets. In recent years, users have higher requirements for the surface appearance of plated steel sheets, and Zn-Al-Mg hot-dip plated steel sheets are required to have a stronger metallic luster.
[0012] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a Zn—Al—Mg-based hot-dip plated steel sheet having a hot-dip plated layer surface having better metallic gloss and better corrosion resistance than conventional steel sheets.
[0013] Means for solving problems
[0014] In order to solve the above-mentioned problems, the present invention adopts the following configuration.
[0015] [1] A Zn-Al-Mg hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet,
[0016] The hot-dip coating layer contains, as an average composition, Al: more than 10 mass % and 22 mass % or less, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities.
[0017] The thickness of the hot-dip coating is set to t, and when a 5 mm square cross section parallel to the surface is exposed at any one of the positions 3t / 4, t / 2 or t / 4 from the surface of the hot-dip coating, the area fraction of the [Zn phase] of the coating structure in at least one of the cross sections is less than 20%.
[0018] [2] A Zn-Al-Mg hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet,
[0019] The hot-dip coating layer contains, as an average composition, Al: more than 10 mass % and 22 mass % or less, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities.
[0020] further comprising one or two selected from the following Group A and Group B,
[0021] The thickness of the hot-dip coating is set to t, and when a 5 mm square cross section parallel to the surface is exposed at any one of the positions 3t / 4, t / 2 or t / 4 from the surface of the hot-dip coating, the area fraction of the [Zn phase] of the coating structure in at least one of the cross sections is less than 20%.
[0022] [Group A] Si: 0.0001 to 2 mass%
[0023] [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2% by mass in total
[0024] [3] A Zn-Al-Mg hot-dip coated steel sheet according to [1] or [2], wherein the ratio (B / A (%)) of the area fraction B of the [Zn phase] of the coating structure in at least one of the above-mentioned cross sections to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is less than 20%.
[0025] [4] The Zn—Al—Mg hot-dip coated steel sheet according to [2], wherein the hot-dip coating layer has an average composition containing the group A in mass %.
[0026] [5] The Zn—Al—Mg hot-dip coated steel sheet according to [2], wherein the hot-dip coating layer has an average composition containing the B group in mass %.
[0027] Effects of the Invention
[0028] According to the present invention, it is possible to provide a Zn—Al—Mg-based hot-dip plated steel sheet having a hot-dip plated layer surface having better metallic gloss and better corrosion resistance than conventional steel sheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic cross-sectional view for explaining an exposed surface for measuring the coating structure of a hot-dip galvanized layer in a Zn—Al—Mg-based hot-dip galvanized steel sheet as an embodiment of the present invention.
[0030] Figure 2 This is a perspective view for explaining an exposed surface for measuring the coating structure of a hot-dip coating layer in a Zn—Al—Mg-based hot-dip coated steel sheet as an embodiment of the present invention. DETAILED DESCRIPTION
[0031] The inventors of the present invention conducted a detailed investigation of the coating of a conventional Zn-Al-Mg hot-dip plated steel sheet having a pear-skin-like appearance. The pear-skin-like appearance is manifested by the presence of a fine glossy portion showing a metallic luster and a fine white portion showing a white color mixed together. The structure of the coating in the glossy portion was investigated, and it was found that the area fraction of the [Zn phase] in the coating surface was reduced compared to that in the white portion. On the other hand, the structure of the coating in the white portion was investigated, and it was found that the ratio of the [Zn phase] to the [ternary eutectic structure of Al / MgZn2 / Zn] was higher than that in the glossy portion.
[0032] Therefore, the inventors of the present invention conducted intensive research to obtain a glossy appearance as a whole by making the glossy portion more present and reducing the white portion in the hot-dip coating, and found that by adjusting the chemical composition of the hot-dip coating and reducing the proportion of the [Zn phase], the surface appearance of the coating as a whole becomes metallic glossy. In addition, it was found that by reducing the proportion of the [Zn phase] to the total of the [ternary eutectic structure of Al / MgZn2 / Zn] and the [Zn phase] in the entire coating, the appearance of the coating becomes more metallic glossy.
[0033] Hereinafter, a Zn—Al—Mg-based hot-dip plated steel sheet as an embodiment of the present invention will be described.
[0034] The Zn-Al-Mg hot-dip plated steel sheet of the present embodiment comprises a steel sheet and a hot-dip plating layer formed on the surface of the steel sheet, wherein the hot-dip plating layer contains Al: more than 10 mass % and less than 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities in terms of average composition, and the thickness of the hot-dip plating layer is set to t, and when a 5 mm square section parallel to the plating surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip plating layer, the area fraction of the [Zn phase] of the plating structure in at least one section becomes less than 20%. Here, the 5 mm square section parallel to the plating surface refers to a square-shaped exposed surface parallel to the surface and having a width of 5 mm square in a top view.
[0035] The steel material that serves as the base of the hot-dip coating layer is not particularly limited in terms of material. As a material, general steel, Al-killed steel, or a portion of high-alloy steel can be applied, and the shape is not particularly limited. In addition, the steel material may be pre-plated with Ni. The hot-dip coating layer of this embodiment is formed by applying the hot-dip coating method described later to the steel material.
[0036] Next, the chemical composition of the hot-dip coating will be described.
[0037] The hot-dip coating layer of the present embodiment contains, in average composition, Al: more than 10 mass % and 22 mass % or less, Mg: 1.0 to 10 mass %, and the remainder includes Zn and impurities.
[0038] One or two selected from the following Group A and Group B may be further contained.
[0039] [Group A] Si: 0.0001 to 2 mass%
[0040] [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2% by mass in total
[0041] The content of Al is in the range of more than 10% by mass and less than 22% by mass based on the average composition. Al is an element required to ensure corrosion resistance. When the content of Al in the hot-dip coating is less than 10% by mass, the effect of improving corrosion resistance becomes insufficient. If it exceeds 22% by mass, although the reason is unknown, the corrosion resistance decreases. From the viewpoint of corrosion resistance, it is preferably set to more than 10% by mass and less than 20% by mass. It is more preferably set to more than 10% by mass and less than 18% by mass. It is more preferably set to more than 11% by mass. In addition, it is more preferably set to less than 19% by mass.
[0042] The content of Mg is in the range of 1.0 to 10% by mass based on the average composition. Mg is an element required to improve the corrosion resistance of the hot-dip coating. When the content of Mg in the hot-dip coating is less than 1.0% by mass, the effect of improving the corrosion resistance becomes insufficient. If it exceeds 10% by mass, the dross generation in the coating bath becomes significant, and it becomes difficult to stably manufacture the plated steel. From the viewpoint of the balance between corrosion resistance and dross generation, it is preferably set to 1.5% by mass or more. In addition, it is preferably set to 8% by mass or less. It is more preferably set to 2% by mass or more. In addition, it is more preferably set to 6% by mass or less.
[0043] In addition, the hot-dip coating may also contain Si in the range of 0.0001 to 2 mass %. Si is an effective element for improving the adhesion of the hot-dip coating. By containing more than 0.0001 mass % of Si, the effect of improving adhesion is shown, so it is preferred to contain more than 0.0001 mass % of Si. On the other hand, even if more than 2 mass % is contained, the effect of improving the adhesion of the coating is saturated, so the content of Si is set to less than 2 mass %. From the viewpoint of coating adhesion, it may also be set to more than 0.01 mass %, and in addition, it may also be set to less than 1 mass %. It may also be further set to more than 0.03 mass %, and in addition, it may also be set to more than 0.8 mass %.
[0044] In addition, any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C may be contained in the hot-dip coating layer in an average composition of 0.0001 to 2 mass %. In addition, the range may be 0.01 to 2 mass %. By containing these elements, the corrosion resistance can be further improved. REM is one or more of the rare earth elements with atomic numbers of 57 to 71 in the periodic table.
[0045] The remainder of the chemical composition of the hot-dip coating is zinc and impurities.
[0046] It should be noted that the composition of the hot-dip galvanized layer can be measured by the following method. It can be obtained by first removing the surface coating with a coating stripper that does not corrode the coating (e.g., NEOREVER SP-751 manufactured by Sancai Chemical Co., Ltd.), dissolving the hot-dip galvanized layer with hydrochloric acid to which an inhibitor (e.g., HIBIRON manufactured by SUGIMURA Chemical Industrial Co., Ltd.) is added, and the resulting solution is subjected to inductively coupled plasma (ICP) emission spectrometry.
[0047] Next, the structure of the hot-dip galvanizing layer will be described. The structure of the hot-dip galvanizing layer of the present embodiment may have the following structure, for example.
[0048] The hot-dip galvanized layer containing Al, Mg and Zn includes [Al phase], [MgZn2 phase], [Zn phase] and [ternary eutectic structure of Al / Zn / MgZn2]. Specifically, it has a form in which [Al phase], [MgZn2 phase] and [Zn phase] are contained in a matrix of [ternary eutectic structure of Al / Zn / MgZn2]. In addition, when Si is contained, [Mg2Si phase] may be contained in the matrix of [ternary eutectic structure of Al / Zn / MgZn2].
[0049] [Ternary eutectic structure of Al / Zn / MgZn2]
[0050] [Ternary eutectic structure of Al / Zn / MgZn2] refers to the ternary eutectic structure of Al phase, Zn phase and intermetallic compound MgZn2 phase. The Al phase forming the ternary eutectic structure is equivalent to, for example, the "Al" phase at high temperature in the ternary equilibrium state diagram of Al-Zn-Mg (which is an Al solid solution with solid dissolved Zn, containing a small amount of Mg).
[0051] The Al" phase at high temperature usually separates into a fine Al phase and a fine Zn phase at room temperature. The Zn phase in the ternary eutectic structure is a Zn solid solution in which a small amount of Al and, depending on the situation, a small amount of Mg is further dissolved. The MgZn2 phase in the ternary eutectic structure is an intermetallic compound phase that exists near Zn: about 84 mass% in the Zn-Mg binary system equilibrium state diagram.
[0052] From the state diagram, it is believed that: no other added elements are dissolved in each phase, or even if dissolved, they are only in very small amounts. However, since their amounts cannot be clearly distinguished by ordinary analysis, the ternary eutectic structure containing these three phases is represented as [ternary eutectic structure of Al / Zn / MgZn2] in this specification.
[0053] 〔Al phase〕
[0054] [Al phase] refers to a phase that has clear boundaries and appears to be island-shaped in the matrix of [ternary eutectic structure of Al / Zn / MgZn2], which is equivalent to the "Al" phase at high temperature in the ternary equilibrium state diagram of Al-Zn-Mg (an Al solid solution with dissolved Zn, containing a small amount of Mg). Regarding this Al" phase at high temperature, the amount of dissolved Zn and Mg varies depending on the Al and Mg concentrations of the plating bath. It is believed that: this Al" phase at high temperature is usually separated into fine Al phase and fine Zn phase at room temperature, but the island shape seen at room temperature is caused by the shape of the Al" phase at high temperature.
[0055] From the state diagram, it is believed that no other added elements are dissolved in this phase, or even if dissolved, they are only in very small amounts. However, since it is impossible to clearly distinguish them through conventional analysis, the phase derived from the Al" phase at high temperature and having a shape derived from the shape of the Al" phase is referred to as "Al phase" in this specification.
[0056] The [Al phase] and the Al phase forming the [ternary eutectic structure of Al / Zn / MgZn2] can be clearly distinguished by microscopic observation.
[0057] 〔Zn phase〕
[0058] The [Zn phase] refers to a phase that has a clear boundary and appears to be an island in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2], but in fact, a small amount of Al and a small amount of Mg may be dissolved in the phase. From the state diagram, it is believed that no other added elements are dissolved in the phase, or even if dissolved, they are extremely small.
[0059] The [Zn phase] is a region where the Zn phase has an equivalent circle diameter of 2.5 μm or more, and can be clearly distinguished from the Zn phase forming the [ternary eutectic structure of Al / Zn / MgZn2] in microscopic observation.
[0060] 〔MgZn2 phase〕
[0061] The [MgZn2 phase] refers to a phase that has a clear boundary and appears to be an island in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2], but in fact, a small amount of Al may be dissolved in it. From the state diagram, it is believed that no other added elements are dissolved in this phase, or even if they are dissolved, they are extremely small.
[0062] The [MgZn2 phase] can be clearly distinguished from the MgZn2 phase that forms the [ternary eutectic structure of Al / Zn / MgZn2] in microscopic observation. In the hot-dip galvanized layer of this embodiment, the [MgZn2 phase] may not be contained depending on the manufacturing conditions, but it will be included in the hot-dip galvanized layer under most manufacturing conditions.
[0063] 〔Mg2Si phase〕
[0064] [Mg2Si phase] refers to a phase that has a clear boundary and appears to be an island in the solidified structure of a hot-dip coating to which Si is added. From the state diagram, it is believed that there is no solid solution of Zn, Al, or other added elements in the [Mg2Si phase], or even if they are solid solution, they are only in very small amounts. The [Mg2Si phase] can be clearly distinguished from other phases in the hot-dip coating under microscopic observation.
[0065] Next, the content of the [Zn phase] is described. In this embodiment, Figure 1 and Figure 2 As shown in , the thickness of the hot-dip coating 2 formed on the steel plate 1 is set to t, and when the hot-dip coating 2 is cut so that a square-shaped exposed surface 3, 4, 5 parallel to the surface 2a and having a width of 5 mm in a top view appears at any position of 3t / 4 position, t / 2 position or t / 4 position from the surface 2a of the hot-dip coating 2, the area fraction of the [Zn phase] of the coating structure becomes less than 20% in at least one of these exposed surfaces 3 to 5. The area fraction of the [Zn phase] may be 15% or less, less than 15%, less than 10%, or less than 5%. By setting the area fraction of the [Zn phase] to less than 20%, the proportion of fine glossy portions showing metallic luster on the surface of the hot-dip coating increases, so that the overall appearance of the hot-dip coating presents a metallic luster. In addition, the lower limit of the area fraction of the [Zn phase] does not need to be specifically limited, but it may be more than 0%, more than 1%, or more than 2%. It should be noted that Figure 1 The cross-sectional diagram shown in FIG. Figure 2 The cross-sectional view is obtained by taking the AA′ plane.
[0066] In addition, in at least one of the exposed surfaces 3 to 5, the ratio (B / A(%)) of the area fraction B of the [Zn phase] of the plating structure to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is preferably less than 20%. The ratio (B / A(%) may be less than 15%, less than 15%, or less than 10%. The lower limit of the ratio (B / A(%)) does not need to be particularly limited, but may be greater than 1%, greater than 2%, or greater than 5%.
[0067] Furthermore, the area fraction of the [Al phase] in the exposed surface where the area fraction of the [Zn phase] is measured may be, for example, 30 to 80 area % or 40 to 65 area %.
[0068] Furthermore, the area fraction of the [ternary eutectic structure of Al / MgZn2 / Zn] in the exposed surface where the area fraction of the [Zn phase] was measured may be, for example, 10 to 75 area % or 20 to 65 area %.
[0069] In addition, the area fraction of the [MgZn2 phase] in the exposed surface where the area fraction of the [Zn phase] is measured may be, for example, 0 to 60 area % or 10 to 40 area %.
[0070] In addition, the area fraction of the [Mg 2 Si phase] in the exposed surface where the area fraction of the [Zn phase] is measured may be, for example, 0 to 5 area % or 0 to 1 area %.
[0071] When a 5 mm square exposed surface 3, 4, 5 is formed parallel to the surface at any position of the 3t / 4 position, t / 2 position or t / 4 position from the surface 2a of the hot-dip coating 2, the hot-dip coating is removed by means such as grinding or argon sputtering. In addition, the exposed surface is preferably made into a mirror surface, for example, the maximum height Rz of the exposed surface is preferably set to 0.2 μm or less. The exposed surface as the observation object can also be an exposed surface at any depth of the 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip coating. The exposed surface at the t / 2 position is preferably selected. In the exposed surface at the t / 2 position, if the area fraction or B / A ratio of the [Zn phase] meets the scope of the present invention, it is highly likely that the area fraction or B / A ratio of the [Zn phase] at other positions also meets the scope of the present invention. More preferably, in the exposed surface at any two depths of 3t / 4 position, t / 2 position or t / 4 position from the hot-dip coating surface, the area fraction of [Zn phase] or the B / A ratio is within the range of the present invention. Further preferably, in the exposed surface at all depths of 3t / 4 position, t / 2 position or t / 4 position from the hot-dip coating surface, the area fraction of [Zn phase] or the B / A ratio is within the range of the present invention.
[0072] For the exposed surface with a size of 5mm×5mm, the plating structure was observed using the secondary electron image of a scanning electron microscope (SEM) to determine the [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn]. When determining each phase and structure, elemental analysis based on the energy dispersive X-ray elemental analysis device attached to the SEM was used to confirm the distribution of Zn, Al and Mg. That is, the area where Zn was mainly detected among Zn, Al and Mg was regarded as the Zn phase, the area where Al was mainly detected was regarded as the Al phase, and the area where Zn and Mg were mainly detected was regarded as the MgZn2 phase. According to the distribution of each detected phase, it was classified into [Al phase], [MgZn2 phase], [Zn phase] and [ternary eutectic structure of Al / Zn / MgZn2] according to the above method. Then, the area fraction of the [Zn phase] in the exposed surface is calculated, and further the ratio of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is calculated (B / A(%)). The [Zn phase] is the region with an equivalent circle diameter of 2.5 μm or more. Thus, the Zn phase in the [ternary eutectic structure of Al / MgZn2 / Zn] is distinguished from the [Zn phase].
[0073] Next, a method for producing the Zn—Al—Mg based hot dip coated steel sheet according to the present embodiment will be described.
[0074] When manufacturing the Zn-Al-Mg hot-dip coated steel sheet of the present embodiment, it is necessary to control the structure of the hot-dip coated layer in such a manner that the area fraction of the [Zn phase] in the exposed surface parallel to the surface at any one of the positions 3t / 4, t / 2 or t / 4 from the surface of the hot-dip coated layer is reduced.
[0075] In order to manufacture Zn-Al-Mg hot-dip plated steel sheets by hot-dip plating, the steel sheets are immersed in a hot-dip plating bath with adjusted chemical composition, so that the molten metal adheres to the surface of the steel sheets. Then, the steel sheets are scooped out of the plating bath, and after the amount of adhesion is controlled by gas wiping, the molten metal is solidified. During solidification, although it also varies depending on the composition, the [Al phase] is formed first, and then as the temperature of the molten metal decreases, the [ternary eutectic structure of Al / Zn / MgZn2] is formed. In addition, in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2], the [MgZn2 phase] and the [Zn phase] are formed. Furthermore, when Si is contained in the hot-dip plating layer, the [Mg2Si phase] is formed in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2].
[0076] It is known that when a coarse [Zn phase] is formed, the ratio of [Al phase] and [MgZn2 phase] in the hot-dip coating increases relatively, and these phases are exposed to the coating surface, so the surface appearance quality decreases. It is estimated that the formation of [Zn phase] is affected by the number of Zn nucleation points. That is, when there are many Zn nucleation points, Zn in the liquid phase before the final solidification is crystallized as a fine Zn phase in the [ternary eutectic structure of Al / Zn / MgZn2]. Therefore, the inventors of the present invention have realized that by increasing the Zn nucleation points, the formation of coarse [Zn phase] can be suppressed, and the surface appearance quality can be improved. As a means to increase the Zn nucleation points, it is considered to make a substance that can become a Zn nucleation point adhere to the surface of the steel plate as the original plate.
[0077] The following describes the details of the production method.
[0078] The hot rolled steel sheet is manufactured and annealed as required. After pickling, cold rolling is performed as required to produce a cold rolled sheet. The hot rolled sheet or cold rolled sheet is degreased and washed with water, and then annealed. The annealed hot rolled sheet or cold rolled sheet is immersed in a hot dip coating bath to form a hot dip coating layer.
[0079] Here, Zn powder is attached to the hot-rolled sheet or cold-rolled sheet before immersion in the hot-dip coating bath, i.e., after annealing. The attached Zn powder will not completely dissolve during hot-dip coating, and becomes a nucleation site for Zn during the final solidification of the coating. A portion of the Zn powder diffuses into the coating bath in a solid state. In the manufacturing method of the present embodiment, this can be achieved only when Zn powder is attached after annealing and before immersion in the coating bath. When Zn powder is attached before annealing, Zn alloys with the steel sheet during annealing, hindering the formation of the hot-dip coating layer. When Zn powder is attached after immersion in the hot-dip coating bath, the attached Zn powder may instead become the cause of the roughening of the surface appearance of the coating. The attached Zn powder may be Zn powder containing Zn and impurities. The average particle size of the Zn powder may be, for example, in the range of 4 to 6 μm. The amount of Zn powder attached may be, for example, 1 to 5 g / m per single side. 2 As long as the average particle size and the amount of adhesion are within this range, the Zn powder can function as a nucleation site for Zn. The adhesion of Zn powder is preferably carried out when the sheet temperature of the hot-rolled sheet or the cold-rolled sheet is within the range of the bath temperature + 10°C to 20°C.
[0080] Next, the steel sheet is immersed in a hot dip coating bath. The hot dip coating bath preferably contains Al: more than 10 mass % and less than 22 mass %, Mg: 1.0 to 10 mass %, and Zn and impurities as the remainder. In addition, the hot dip coating bath may also contain Si: 0.0001 to 2 mass %. Furthermore, the hot dip coating bath may also contain any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in a total of 0.0001 to 2 mass %.
[0081] The temperature of the hot-dip coating bath is preferably in the range of 400 to 500° C. This is because a desired hot-dip coating layer can be formed when the temperature of the hot-dip coating bath is in this range.
[0082] The amount of hot-dip coating can be adjusted by gas wiping or other means on the steel sheet taken out of the hot-dip coating bath. The amount of hot-dip coating is preferably adjusted to a total of 30 to 600 g / m2 on both sides of the steel sheet. 2 When the adhesion is less than 30g / m 2 In the case of Zn-Al-Mg hot-dip coated steel sheet, the corrosion resistance is reduced, which is not preferred. 2 In the case of , the molten metal attached to the steel sheet will drip, making it impossible to smooth the surface of the hot-dip coating, which is not preferred.
[0083] After adjusting the amount of hot-dip coating, the steel sheet is cooled. The cooling of the molten metal attached to the steel sheet begins after the steel sheet is taken out of the hot-dip coating bath. Although it also varies depending on the composition of the hot-dip coating bath, [Al phase] begins to crystallize at around 430°C. Then, [MgZn2] begins to crystallize at around 370°C, [ternary eutectic structure of Al / Zn / MgZn2] crystallizes at around 340°C, and then [Zn phase] crystallizes to complete solidification.
[0084] At this time, since a large amount of Zn powder attached to the steel plate acts as a nucleation point for Zn, the Zn in the liquid phase is formed as a fine Zn phase in the [ternary eutectic structure of Al / Zn / MgZn2]. On the other hand, the formation of a coarse Zn phase ([Zn phase]) having an equivalent circle diameter of more than 2.5 μm can be suppressed.
[0085] When a chemical conversion treatment layer is formed on the surface of the hot-dip coating layer, the hot-dip coated steel sheet after the hot-dip coating layer is subjected to a chemical conversion treatment. The type of chemical conversion treatment is not particularly limited, and a known chemical conversion treatment can be used.
[0086] When a coating layer is formed on the surface of the hot-dip coating layer or the surface of the chemical conversion treatment layer, the hot-dip coated steel sheet after the hot-dip coating layer or the chemical conversion treatment layer is subjected to a coating treatment. The type of coating treatment is not particularly limited, and a known coating treatment can be used.
[0087] As described above, according to the present embodiment, the metallic glossiness of the hot-dip coating surface can be improved more than before.
[0088] Example
[0089] Next, the embodiment of the present invention is described. The cold-rolled steel sheet is degreased and washed. Thereafter, the steel sheet is cold-rolled and annealed. For the cold-rolled and annealed steel sheet, 1 to 5 g / m2 of grease is applied to each side. 2 The Zn powder with an average particle size of 4 to 6 μm was attached, immersed in a hot-dip bath and then picked up. Thereafter, the attachment amount was adjusted by gas wiping and further cooled. It should be noted that, for No. 67, annealing and hot-dip plating were performed after the Zn powder was attached, and for No. 68, Zn powder was attached after hot-dip plating, and further, for No. 69, hot-dip plating was performed without the attachment of Zn powder. In this way, the hot-dip plated steel sheets No. 1 to 69 shown in Table 1A and Table 2B were manufactured.
[0090] For the obtained hot-dip galvanized steel sheet, Figure 1 As shown in , a 5 mm square exposed surface parallel to the surface is formed at the t / 4 position, t / 2 position and 3t / 4 position from the surface of the hot-dip galvanized layer. The exposed surface is formed by removing the hot-dip galvanized layer by grinding and then mirror-polishing.
[0091] For each exposed surface of 5mm×5mm size, the plating structure was observed using the secondary electron image of a scanning electron microscope (SEM) to determine the [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn]. When determining each phase and structure, elemental analysis based on the energy dispersive X-ray elemental analysis device attached to the SEM was used to confirm the distribution of Zn, Al and Mg. Then, the area fraction of the [Zn phase] in each exposed surface was calculated, and the ratio of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] (B / A(%)) was further calculated. [Zn phase] is the area with an equivalent circle diameter of 2.5μm or more measured as [Zn phase]. In this way, the Zn phase in the [ternary eutectic structure of Al / MgZn2 / Zn] is distinguished from the [Zn phase].
[0092] The results are shown in Tables 2A and 2B.
[0093] In addition, in the exposed surfaces of No. 1 to 62 where the area fraction of [Zn phase] was measured, the area fraction of [Al phase] was in the range of 30 to 80 area %, the area fraction of [ternary eutectic structure of Al / MgZn2 / Zn] was in the range of 10 to 75 area %, the area fraction of [MgZn2 phase] was in the range of 0 to 60 area %, and the area fraction of [Mg2Si phase] was in the range of 0 to 5 area %.
[0094] Furthermore, the surface of the hot-dip coating layer of the obtained hot-dip coated steel sheet was observed and visually evaluated based on the following criteria. A and B were considered acceptable. The results are shown in Tables 2A and 2B.
[0095] A: No appearance spots other than glossiness can be observed even from 0.5 m in front.
[0096] B: Appearance spots other than gloss were observed from 0.5 m forward, but no appearance spots other than gloss were observed from 2 m forward.
[0097] C: Appearance spots other than gloss were also observed from 2 m in front.
[0098] The corrosion resistance of hot-dip galvanized steel sheets is evaluated by the corrosion loss after the CCT test. The plated steel sheets were cut into 150×70 mm pieces and the CCT according to JASO-M609 was used to investigate the corrosion loss after 30 cycles of CCT. The evaluation was based on the corrosion loss of less than 30 g / m 2 Set to F, and set the corrosion reduction to 30g / m 2 Above and below 50g / m 2 Set to G, and set the corrosion reduction to 50g / m 2 The above was defined as P, and F and G were defined as pass. The results are shown in Tables 2A and 2B.
[0099] Since the chemical composition of the hot-dip coating of the hot-dip coating of No. 1 to No. 62 steel sheets is within the range of the present invention, Zn powder is attached after annealing and before hot-dip coating, so Zn powder functions as each generation site of Zn during the solidification of the hot-dip coating. As a result, when an exposed surface of 5 mm square is formed at the 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip coating, the area fraction of the coating structure (Zn phase) in at least one exposed surface becomes less than 20%. Therefore, the appearance of the hot-dip coating becomes a glossy appearance. In addition, the corrosion resistance is also good.
[0100] The hot-dip plated steel sheet No. 63 has low corrosion resistance because the Al content in the hot-dip plated layer is small.
[0101] The hot-dip plated steel sheet No. 64 had an excessive Al content in the hot-dip plated layer, so the corrosion resistance was reduced.
[0102] The hot-dip plated steel sheet No. 65 has low corrosion resistance because the Mg content of the hot-dip plated layer is small.
[0103] The hot-dip plated steel sheet No. 66 has an excessive Mg content in the hot-dip plated layer, so the corrosion resistance is reduced. In addition, the area fraction of the [Zn phase] in the plated structure is 20% or more, and the glossiness of the hot-dip plated layer is insufficient.
[0104] Since the hot-dip plated steel sheet No. 67 was annealed and hot-dip plated after the Zn powder was attached, the Zn powder alloyed with the steel sheet during annealing and did not function as a nucleation site for Zn. Therefore, the area fraction of the [Zn phase] at the position 3t / 4, the position t / 2, or the position t / 4 from the surface of the hot-dip plated layer was all 20% or more, and the glossiness of the appearance of the hot-dip plated layer became insufficient.
[0105] In the hot-dip plated steel sheet No. 68, Zn powder adhered after hot-dip plating, so the Zn powder did not function as a nucleation site for Zn. Therefore, the area fraction of the [Zn phase] at the position 3t / 4, t / 2, or t / 4 from the surface of the hot-dip plated layer was all 20% or more, and the glossiness of the appearance of the hot-dip plated layer became insufficient.
[0106] Since the hot-dip plated steel sheet No. 69 had no Zn powder attached, the Zn powder did not function as a nucleation site for Zn. Therefore, the area fraction of the [Zn phase] at the position 3t / 4, t / 2, or t / 4 from the surface of the hot-dip plated layer was all 20% or more, and the glossiness of the appearance of the hot-dip plated layer became insufficient.
[0107] [Table 1A]
[0108]
[0109] [Table 1B]
[0110]
[0111] The underlined part indicates that it is outside the scope of the present invention.
[0112] [Table 2A]
[0113]
[0114] [Table 2B]
[0115]
[0116] The underlined part indicates that it is outside the scope of the present invention.
[0117] Industrial Applicability
[0118] The Zn—Al—Mg-based hot-dip plated steel sheet disclosed herein has excellent metallic gloss on the surface of the hot-dip plated layer and excellent corrosion resistance, and therefore has high industrial applicability.
[0119] Explanation of symbols
[0120] 1 Steel plate, 2 Hot-dip coating, 2a Surface of hot-dip coating, 3 Cross section at t / 4 position (exposed surface), 4 Cross section at t / 2 position (exposed surface), 5 Cross section at 3t / 4 position (exposed surface).
Claims
1. A Zn-Al-Mg hot-dip coated steel sheet, characterized in that: The invention comprises a steel plate and a hot-dip coating layer formed on the surface of the steel plate. The hot-dip coating layer contains, as an average composition, more than 10 mass % and 22 mass % or less of Al, 1.0 to 10 mass % of Mg, and the remainder of Zn and impurities. The thickness of the hot-dip galvanized layer is set to t, and when a 5 mm square cross section parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip galvanized layer, the area fraction of the [Zn phase] of the plating structure in at least one of the cross sections is less than 20%.
2. A Zn-Al-Mg hot-dip coated steel sheet, characterized in that: The invention comprises a steel plate and a hot-dip coating layer formed on the surface of the steel plate. The hot-dip coating layer contains, as an average composition, more than 10 mass % and 22 mass % or less of Al, 1.0 to 10 mass % of Mg, and the remainder of Zn and impurities. further comprising one or two selected from the following Group A and Group B, The thickness of the hot-dip coating is set to t, and when a 5 mm square cross section parallel to the surface is exposed at any one of the positions 3t / 4, t / 2 or t / 4 from the surface of the hot-dip coating, the area fraction of the [Zn phase] of the coating structure in at least one of the cross sections is less than 20%, [Group A] Si: 0.0001 to 2 mass% [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: the total is 0.0001 to 2 mass %.
3. The Zn-Al-Mg hot-dip coated steel sheet according to claim 1 or claim 2, wherein: The ratio (B / A (%)) of the area fraction B of the [Zn phase] of the plating structure in at least one of the cross sections to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is less than 20%.
4. The Zn-Al-Mg hot-dip plated steel sheet according to claim 2, wherein: The hot-dip coating layer has an average composition containing the group A in mass %.
5. The Zn-Al-Mg hot-dip coated steel sheet according to claim 2, wherein: The hot-dip coating layer has an average composition containing the B group in mass %.
Citation Information
Patent Citations
Hot dip zinc-aluminum-magnesium plated steel sheet good in corrosion resistance and surface appearance and its production
JP1998226865A
Hot dip zn-al-mg coated steel sheet excellent in corrosion resistance and external surface appearance, and its production
JP1998306357A
Hot-dip zn-al-mg plated steel sheet superior in workability and corrosion resistance, and manufacturing method therefor
JP2004068075A
Method and device for optical gear measurement
JP2022094346A